Interval Training in Men at Risk for Insulin Resistance - Earnest, C. P.; Lupo, M.; Thibodaux, J.; Hollier, C.; Butitta, B.; Lejeune, E.; Johannsen, N. M.; Gibala, M. J.; Church, T. S. (International Journal of Sports Medicine, 2013)
We compared 3 months of eucaloric (12 kcal/kg/wk) steady state aerobic training (AER) to interval training (INT) in men at risk for insulin resistance. Primary outcomes included oral glucose tolerance testing (OGTT) and HOMA-IR 24 h and 72 h after each participants last exercise session. Secondary outcomes were VO2max, anthropometry, and metabolic syndrome expressed as a summed z-score (zMS). We also performed a sub-analysis for participants entering the trial above and below the HOMA-IR study median. Mean (95% CI) AER ( − 12.81 mg/dl;  − 24.7,  − 1.0) and INT ( − 14.26 mg/dl;  − 24.9,  − 3.6) significantly improved 24 h OGTT. HOMA-IR did not improve for AER, but did for INT 24 h and 72 h post-exercise. VO2max improved similarly for both groups. Changes in body mass for INT ( − 2.29 kg;  − 3.51,  − 1.14), AER, ( − 1.32 kg;  − 2.62, 0.58)] and percent body fat [INT,  − 0.83%; − 1.62,  − 0.03), AER ( − 0.17%;  − 1.07, 0.06)] were only significant for INT. When examined as a full cohort, zMS improved for both groups. Upon HOMA-IR stratification, only high HOMA-IR AER showed significant improvements, while both low and high INT HOMA-IR participants demonstrated significant reductions (P<0.05). Eucaloric AER and INT appear to affect fasting glucose, OGTT and VO2max similarly, while INT may have a greater impact on HOMA-IR and zMS.
Keywords: exercise; insulin resistance; insulin sensitivity; glucose control; diabetes